The Emerging Role of Ewingella Americana in Cancer Therapy (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Recent advancements in oncological research have highlighted the vast therapeutic potential residing within unexplored microbial ecosystems. This study investigates the antitumor efficacy of a naturally occurring bacterium, Ewingella americana, isolated from the intestines of the Japanese tree frog. Amphibians rarely develop cancer, and their microbiomes have emerged as a unique source for novel therapeutic agents. In preclinical mouse models of colorectal cancer, a single intravenous administration of Ewingella americana achieved complete tumor elimination, outperforming several conventional cancer treatments. The bacterium operates through a dual-action mechanism: first, as a facultative anaerobe, it selectively accumulates and proliferates rapidly within the hypoxic microenvironment of tumors, exerting direct cytotoxic effects on cancer cells without colonizing healthy organs. Second, its presence robustly stimulates the host immune system, recruiting an influx of T cells, B cells, and neutrophils to the tumor site. This immune activation establishes lasting systemic responses, helping to prevent tumor regrowth. Comprehensive safety evaluations demonstrated that the bacteria are rapidly cleared from the bloodstream and do not induce chronic toxicity. These findings establish a solid proof-of-concept for the use of naturally occurring amphibian intestinal bacteria as an effective, tumor-specific cancer therapy, opening promising
Keywords: Anti-tumour; ewingella Americana; tumour regrowth; cancer therapy; cancer cells